Identyfikacja i prezentacja wspólnych przedsięwzięć w sprawozdaniu finansowym - Tatarska, Marzena (Identification and Presentation of Joint Ventures in the Financial Statement, 2007)
This article gives the definitions of joint ventures based on the specialist literature and standards of accounting and the most important problems of joint ventures accounting in certain countries: Canada, Great Britain and the United States of America. The article presents the main recommendations of Group G4+1. The author of the article shows the lack of cohesion of legal regulations in certain countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 287-318